Change of Paradigm: From Social Sciences to Research on Art - Barranco Martos, Norah (2017)
The autor points at the importance of comprising the subjective and creative abilities of human beings in the approach to social reality. Using her own experience as a sociologist, she embraces us to become aware of the limitations that scientific method imposes, which can be surpassed through an artistic investigation as a modular epistemological model that offers the possibility of combining investigation, methodology, creativity, objectivity, subjectivity, knowledge and intervention in a sole sequence, much more similar to human being´s way of feeling and being.